2014
DOI: 10.1007/s10620-013-2928-y
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption Is Associated with Esophageal Cancer Risk in a Meat- and Cancer-Histological-Type Dependent Manner

Abstract: Meat consumption is associated with esophageal cancer risk, which depends on meat type and histological type of esophageal cancer. High intake of red meat and low intake of poultry are associated with an increased risk of esophageal squamous cell carcinoma. High meat intake, especially processed meat, is likely to increase esophageal adenocarcinoma risk. And fish consumption may not be associated with incidence of esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 55 publications
2
42
1
1
Order By: Relevance
“…It is common for healthy diet patterns, including the DASH (3), American Heart Association diet (7), and Mediterranean diet (24), to recommend limiting red meat consumption on the basis of concerns regarding saturated fat and sodium contents and a positive correlation between consumption of red meat and mortality (25,26), cardiovascular disease (27,28), and cancer (29)(30)(31). However, the extent of processing may have a modulating effect on these relations.…”
Section: Bpmentioning
confidence: 99%
“…It is common for healthy diet patterns, including the DASH (3), American Heart Association diet (7), and Mediterranean diet (24), to recommend limiting red meat consumption on the basis of concerns regarding saturated fat and sodium contents and a positive correlation between consumption of red meat and mortality (25,26), cardiovascular disease (27,28), and cancer (29)(30)(31). However, the extent of processing may have a modulating effect on these relations.…”
Section: Bpmentioning
confidence: 99%
“…As summarized in a recent meta-analysis, the association between meat and EC varied with meat type and histologic type of EC. 29 The definition and components of processed meat might be different among studies, which yielded inconsistent results on processed meat and EC. 19 In this study, salted meat was almost the only type of processed meat consumed in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…15 For oesophageal cancer two cohort studies suggested a non-significant positive association with processed meat in extreme categories analyses, while for red meat the conclusions came from case-control studies, for which eight of ten found a positive association (table I). Another four meta-analyses confirmed an increased risk of both squamous and adenocarcinoma with higher red and/or processed meat intake, 19,20,23,25 however, there is evidence for heterogeneity by the cancer subtype. 21 For pancreatic cancer, red meat intake indicated a nonsignificantly increased risk, while for processed meat the association was significant (table I).…”
Section: Artículo Especialmentioning
confidence: 98%